Fabrication and operational characteristics of step-down piezoelectric transformer based on PMN-PT ceramics - Magalhaes, A. L.; Oliveira, A. F.; Sales, A. J. M.; Aquino, F. J. A.; Gouveia, D. X.; Menezes, J. W. M.; Araujo, E. B. [UNESP]; Sombra, A. S. B. (Taylor & Francis Ltd, 2018)
A ring-type step-down piezoelectric transformer based on 0.65Pb (Mg1/2Nb2/3)O-3-0.35PbTiO(3) ceramic was manufactured to study its main operational characteristics through experimental measurements and numerical simulations based on the corresponding electrical equivalent circuit. The measured resonance frequency of 93.4 kHz was observed for the first vibration mode and the measured voltage gain and maximum efficiency were 0.1 and 49.3%, respectively, for the load resistance of 500X. The simulated voltage gain and maximum efficiency were 44.3% and 0.1 at 733X. The possible origin of the low efficiency in the studied piezoelectric transformer is discussed.
Keywords: Piezoelectric transformer; PMN-PT; ceramics